2019
DOI: 10.1038/s41598-019-45994-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in response to environmental stresses in the fungal plant pathogen Zymoseptoria tritici

Abstract: During their life cycles, pathogens have to adapt to many biotic and abiotic environmental stresses to maximize their overall fitness. Morphological transitions are one of the least understood of the many strategies employed by fungal plant pathogens to adapt to constantly changing environments, even though different morphotypes may play important biological roles. Here, we first show that blastospores (the “yeast-like” form of the pathogen typically known only under laboratory conditions) can form from germin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
101
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(127 citation statements)
references
References 86 publications
10
101
0
Order By: Relevance
“…Plant pathogens typically experience nutrient limitations while growing on leaves and the perception of a nutrient-limited environment may act as a stimulus to induce cell fusion in foliar plant pathogens. Both germinating blastospores or pycnidiospores of Z. tritici undergo CAT and VHF in vitro and in planta , supporting our previous observation (Francisco et al, 2019). Thus, we demonstrated that vegetative cell fusions occur independently of the morphotype and it may have an important contribution to the lifestyle of Z. tritici during the plant-pathogen interaction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Plant pathogens typically experience nutrient limitations while growing on leaves and the perception of a nutrient-limited environment may act as a stimulus to induce cell fusion in foliar plant pathogens. Both germinating blastospores or pycnidiospores of Z. tritici undergo CAT and VHF in vitro and in planta , supporting our previous observation (Francisco et al, 2019). Thus, we demonstrated that vegetative cell fusions occur independently of the morphotype and it may have an important contribution to the lifestyle of Z. tritici during the plant-pathogen interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Z. tritici alters its growth morphology in detrimental to the nutritional conditions (Francisco et al , 2019). To assess whether vegetative cell fusion affects fungal growth, we determined the radial growth of ΔZtKu70, ΔZtSo, and ΔZtSo -comp on different culture media.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in carrying capacity for the ∆ Zt107320 strains could be indicative of an earlier nutrient limitation due to lower efficiency in nutrient usage. This nutrient limitation could therefore be responsible for the more pronounced switch to hyphal growth, in particular, since carbon limitation increases mycelial growth (Francisco et al , ). This is further supported by the fact that 24 h after inoculation onto solid MM no differences in growth pattern were observable between the wild type, the Zt107320 deletion and complementation strains (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For isolates 1A5, 1E4, 3D1 and 3D7, RNA sequencing experiments on minimal media were performed by [45,67]. Raw reads were retrieved from the NCBI Short Read Archive accession number SRP077418.…”
Section: Rna Extraction Library Preparation Sequencing and Quantifimentioning
confidence: 99%